Biochemical Dissection of the ATPase TraB, the VirB4 Homologue of the Escherichia coli pKM101 Conjugation Machinery - Durand, Eric (American Society for Microbiology (ASM), 2010)
Type IV secretion (T4S) systems are involved in several secretion processes, including secretion of virulence factors, such as toxins or transforming molecules, or bacterial conjugation whereby two mating bacteria exchange genetic material. T4S systems are generally composed of 12 protein components, three of which, termed VirB4, VirB11, and VirD4, are ATPases. VirB4 is the largest protein of the T4S system, is known to play a central role, and interacts with many other T4S system proteins. In this study, we have biochemically characterized the protein TraB, a VirB4 homologue from the pKM101 conjugation T4S system. We demonstrated that TraB is a modular protein, composed of two domains, both able to bind DNA in a non-sequence-specific manner. Surprisingly, both TraB N- and C-terminal domains can bind ATP, revealing a new degenerated nucleotide-binding site in the TraB N-terminal domain. TraB purified from the membrane forms stable dimers and is unable to hydrolyze ATP while, when purified from the soluble fraction, TraB can form hexamers capable of hydrolyzing ATP. Remarkably, both the N- and C-terminal domains display ATP-hydrolyzing activity. These properties define a new class of VirB4 proteins.